Case Report: Superior mesenteric artery vasculitis causing aneurysm following COVID-19 infection - Kim, Minju; Han, Jeong Hee; Choi, Jung Bum; Lee, Byoung Chul; Jung, Hyuk Jae (Frontiers in Surgery, 2024)
Objective: Arteritis refers to all infectious and noninfectious conditions leading to inflammation of the arterial wall. However, little is known about its presence in patients with coronavirus disease 2019 . Most patients improved with steroids along with conservative treatments in a few studies. We report our experience with superior mesenteric artery (SMA) arteritis causing an aneurysm following COVID-19 infection. Case presentation: A 66-year-old female patient infected with COVID-19 1 month prior presented with abdominal pain. A computed tomography scan showed proximal SMA arteritis. Although a preliminary antibacterial treatment was initiated, the follow-up CT revealed an aggressive and fast-growing 5.7 cm-sized SMA aneurysm. Subsequently, an open interposition bypass of the SMA aneurysm was performed successfully. As the specimens retrieved during surgery showed no bacterial colonization in the tissue or blood cultures, the patient was discharged without complications. Conclusions: The mechanism of arteritis in patients with COVID-19 has not been elucidated. In the absence of evidence of bacterial infection in arteritis, it is necessary to consider the possibility of viral infection caused by COVID-19 during the COVID-19 pandemic era and start with high-dose steroid therapy promptly.